Assessing the impact of a new health sector pay system upon NHS staff in England - Buchan James; Evans David (BMC, 2008)
Abstract Background Pay and pay systems are a critical element in any health sector human resource strategy. Changing a pay system can be one strategy to achieve or sustain organizational change. This paper reports on the design and implementation of a completely new pay system in the National Health Service (NHS) in England. 'Agenda for Change' constituted the largest-ever attempt to introduce a new pay system in the UK public services, covering more than one million staff. Its objectives were to improve the delivery of patient care as well as enhance staff recruitment, retention and motivation, and to facilitate new ways of working. Methods This study was the first independent assessment of the impact of Agenda for Change at a local and national level. The methods used in the research were a literature review; review of 'grey' unpublished documentation provided by key stakeholders in the process; analysis of available data; interviews with key national informants (representing government, employers and trade unions), and case studies conducted with senior human resource managers in ten NHS hospitals in England Results Most of the NHS trust managers interviewed were in favour of Agenda for Change, believing it would assist in delivering improvements in patient care and staff experience. The main benefits highlighted were: 'fairness', moving different staff groups on to harmonized conditions; equal pay claim 'protection'; and scope to introduce new roles and working practices. Conclusion Agenda for Change took several years to design, and has only recently been implemented. Its very scale and central importance to NHS costs and delivery of care argues for a full assessment at an early stage so that lessons can be learned and any necessary changes made. This paper highlights weaknesses in evaluation and limitations in progress. The absence of systematically derived and applied impact indicators makes it difficult to assess impact and impact variations. Similarly, the lack of any full and systematic evaluation constrained the overall potential for Agenda for Change to deliver improvements to the NHS.